Preparation, characterization and application of Zeolite-Y (Na-Y) for water filtration - Rahman, Md. Mokhlesur; M. B., Awang (2011)
Advancement and innovation in developing water filtering system enhances immensely in the field of water purification. In this study the acid treated rice husk ash was used as SiO2 source in the preparation of zeolite Y, a medium siliceous zeolite used as an ion exchangers in water treatment process. Purity, pore size distribution, FT-IR and SEM micrographs of treated and non-treated samples are presented. The powdered (semi solid) zeolite Y products were characterized by XRD and FT-IR and pore size distribution was characterized by Micromeritics Instrument. Obtained zeolite Y, BET surface area 621.18 square meters per gram, pore volume is 0.33 cubic centimeters per gram and its average pore diameter is 21.22 Å. The DDW was produced by developed a new type of filtering system using most effective and highly efficient nano-materials. The aforementioned system involved coagulation, chlorination, sand treatment, and activated carbon purification and nylon polisher layers.